Knowledge management system enabling collaboration in industry cluster - Sureephong P. (2014)
The knowledge-based economy forces SMEs to form as strategic alliance in order to compete in the world market. In the meantime, the concept of the industry cluster was widely implemented in many countries for improving the competitiveness of their industries. The cluster development relies on two key success factors which are knowledge sharing and collaboration among the actors. Thus, our study proposes a Knowledge Management System (KMS) to support the knowledge activities within the industry cluster. Therefore, the objectives of this paper are set to capture, create and represent knowledge and ontology by using the knowledge engineering approach. Copyright © 2010 Inderscience Enterprises Ltd.